2014
DOI: 10.1159/000362647
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Nuclear Factor of Activated T Cells c3 Modulates the Function of Macrophages in Sepsis

Abstract: The role of the transcription factor nuclear factor of activated T cells (NFAT) was initially identified in T and B cell gene expression, but its role in regulating gene expression in macrophages during sepsis is not known. Our data show that NFATc3 regulates expression of inducible nitric oxide synthase (iNOS) in macrophages stimulated with lipopolysaccharide. Selective inhibition of NFAT by cyclosporine A and a competitive peptide inhibitor 11R-VIVIT inhibited endotoxin-induced expression of iNOS and nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Macrophages were pretreated with hemozoin and stimulated with - IFNγ [100 ng/ml] (BD Pharmingen), LPS [1 μg/ml] (Alexis Biochemicals) and IL4 [20 ng/ml] (RnD Systems), and processed for Western immunoblotting for iNOS as described previously [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Macrophages were pretreated with hemozoin and stimulated with - IFNγ [100 ng/ml] (BD Pharmingen), LPS [1 μg/ml] (Alexis Biochemicals) and IL4 [20 ng/ml] (RnD Systems), and processed for Western immunoblotting for iNOS as described previously [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Evidence shows that CsA blocks NFAT binding to the inducible NO synthase (iNOS) promoter, causing a reduction of iNOS expression and nitrite production in macrophages (14,15). CsA can also down-regulate the enzyme cyclooxygenase-2 (COX-2) in the kidney, which converts arachidonic acid into prostaglandin E2 (PGE2), an inflammatory mediator that modulates vascular permeability to expedite immune cell recruitment (16,17).…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…The inhibition of nFaT was revealed to be an effective method for reducing the multiple inflammatory cytokines induced by TnF-α in human retinal microvascular endothelial cells (16), thus further highlighting nFaT signaling as a potential anti-inflammatory target. Recent studies (17,18) have revealed that NFATc3 is a key molecular regulator of sepsis-induced lung injury. notably, nFaTc4 has been suggested to be a pivotal regulatory event in endothelial cell inflammation (15), which is an early step in the development of lung injury.…”
Section: Introductionmentioning
confidence: 99%